THE INFLUENCE OF COMPANY LEVEL ON AUDIT QUALITY IN INDONESIA'S LISTED BANKING COMPANIES - Imas Nurani Islami; Kamola Ashirova; Memen Kustiawan; Gulnora Bekimbetova (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study analyzes the influence of firm-level factors, as proxied by technology investment, on audit quality based on auditor decisions (in Big Four versus Non-Big Four companies), for banking companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Based on agency theory, signaling theory, and the resource-based view (RBV), banks with higher organizational levels tend to hire reputable external auditors to minimize information asymmetry and convey financial reliability to stakeholders. Using a quantitative approach with purposive sampling, data was obtained from 60 companies for annual observations, which were then analyzed using binary logistic regression. The results show that the average technology investment (in natural logarithm) is 25.3963, with a standard deviation of 2.053, reflecting substantial variation across banks. Approximately 60% of cases involve Big Four auditors. The binary logistic regression results indicate a statistically significant and positive relationship between firm-level technology investment and audit quality (Wald = 5.571, p = 0.018, Exp(B) = 1.417), although the model explains a modest proportion of variance (Nagelkerke R² = 0.135), suggesting that additional predictors may further improve explanatory power in future research.